Effect of organic farming practices on soil health improvement of Coconut farms - Nghia, Nguyen Khoi; Robatjazi, Javad; Vy, Vo Duyen Thao; Tecimen, Hüseyin Barış; Lasar, Hendra Gonsalve W.; Lesueur, Didier; Bai, Shahla Hosseini; Tran, Huu-Tuan; Thien, Nguyen Huu; Luan, Do Thanh (Elsevier, 2025)
The present study aimed to provide data on what extend of organic management (OF) improve soil health compared to conventional farms (CF). In this study, a total of 24 top soil samples (0–30 cm) were collected from Mo Cay Nam and Mo Cay Bac, Ben Tre, Vietnam, representing organic vs conventional farm soils, respectively to analyze farming systems in terms of the chemical, physical, and biological soil properties. Soil nutrients, soil microbial density, dehydrogenase enzyme activity and soil bacteria diversity were detected using atomic absorption spectrometry, serial dilution and plating; triphenyl formazan detection, and DNA extraction using Invitrogen™ and Qubit™, respectively. Our results indicated that soil bulk density was 11 % lower and soil porosity was 4 % higher, respectively at organic farms compared to the conventional farms. Meanwhile, both soil NH4+ and available phosphorus contents were higher in the organic farming soils (38.9 mg kg−1 and 69.0 mg kg−1, respectively). Total soil bacteria and cellulose-decomposing bacteria were found to be insignificantly lower in conventional farms (CF) as compared to organic farms (OF) (6.01 log CFU g−1 soil vs 6.26 log CFU g−1 soil) and (3.82 log CFU g−1 soil vs 4.18 log CFU g−1 soil), respectively. The beta diversity of soil bacterial community, along with the bacterial orders Bacillales, Frankiales, Elsterales, Pseudomonadales, and Pedosphaerales exhibited higher with organic farming practices and dehydrogenase enzyme activity in organic farms (OF) was significantly higher (0.61 µg TPF g−1 soil hour−1) as compared to 0.47 µg TPF g−1 soil hour−1 in conventional farms (CF). This study demonstrates the benefits of organic management on soil health in coconut plantations and promotes the overall health of coconut orchards.